Bronchoscopy in lipoid pneumonia. Issue 11 (November 1992) - Kameswaran, M; Annobil, S H; Benjamin, B; Salim, M
Abstract : Forcible administration of rendered animal fat to infants is a tradition in south western Saudi Arabia. Accidental inhalation may result in a resistant form of lipoid pneumonia. A series of 24 cases of lipoid pneumonia, 22 of which were diagnosed by bronchoscopy with bronchial lavage and microscopic examination of the aspirate, are reported. The technique is described briefly and the results analysed. A high index of suspicion together with bronchoscopy and bronchial lavage of all cases of resistant or recurrent pneumonia is essential in areas such as ours for diagnosis of this condition.